Membangun Generasi Berkarakter melalui Kolaborasi Orang Tua dan Sekolah dalam Program Tahfidz SD/MI - Diyah Andini Kusumastuti; Nur Khasanah (Asosiasi Seni Desain dan Komunikasi Visual Indonesia, 2025)
The development of the increasingly advanced times brings serious challenges to the formation of the character of the younger generation, especially at the elementary school levels. The phenomenon of declining religious values, discipline, and responsibility for students is a crucial issue that needs to be addressed immediately. This study aims to analyze the collaboration model between parents and schools in supporting tahfidz programs and their contribution to the formation of religious character, discipline, and student responsibility. The research method uses the Systematic Literature Review (SLR) approach by examining various relevant previous research results, as well as a qualitative descriptive approach to understand the dynamics of the collaboration. The results of the study show that strong collaboration between parents and schools in the tahfidz program has a significant impact on the formation of students' character. Effective forms of collaboration include intensive communication, active participation in the tahfidz process, and moral and material support at home. Children who receive optimal assistance from their parents tend to show stronger religious character, discipline in managing time, and a higher sense of responsibility for memorization. On the contrary, limited parental time, lack of understanding of memorization methods, and differences in commitment are the main inhibiting factors in the success of the program. The conclusion of this study emphasizes that synergy between parents and schools is the main key to the success of the tahfidz program to build a generation of character. Recommendations for schools are to strengthen the communication system with parents, provide training in memorization techniques for families, and create a conducive learning environment both at school and at home. Further research is recommended to involve field studies to get a more comprehensive picture of the implementation of this collaboration.